PENINGKATKAN HASIL BELAJAR MELALUI MODEL PEMBELAJARAN TEAM GAME TOURNAMENT (TGT) PADA PESERTA DIDIK KELAS V SDN PUTAT JAYA IV/380 SURABAYA - Putri Roudhotul Jannah; Meilantifa; Nurul Aini (JIP: Jurnal Ilmu Pendidikan, 2025)
This study aims to evaluate the improvement ini student learning outcomes through the implementation oh the Team Game Tournament (TGT) learning model in the Indonesian language subject, focusing on the use of the pe-an affix, in Class V at SD Negeri Putat Jaya IV/380 Surabaya. The research was motivated by previously low student achievement in this subject area. The study employed a Classtoom Action Research approach and was conducted in Class V-A, involving 29 students. Data were collected through teacher assessments and observational notes during the learning process. The research was carried out over two cycles, with each cycle consisting of planning, action, observation, and reflection stages. The results indicated a significant improvement in student learning outcomes. From Cycle I to Cycle II, the percentage of students achieving the learning objectives increased from 76% to 86%, showing a 10% improvement. These findings demonstrate that the use of the TGT learning model effectively enhanced the students understanding of the pe-an affix and exposition texts in the Indonesian language subject.